Ductal eccrine carcinoma of the axilla: a diagnostic pitfall - Maria Helena Toda Sanches de Brito; Cecília Silva Nunes de Moura Dionísio; Joana Cintia Monteiro Ferreira; Maria Joaninha Madalena de Palma Mendonça da Costa Rosa; Fernando Petrucci Bernardo e Cunha; Maria Manuela Antunes Pecegueiro da Silva Garcia (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Ductal eccrine carcinoma (DEC) is a rare sweat gland carcinoma with ductular differentiation. Clinically, it is characterized by a slowly growing, hardened plaque or nodule predominantly located on the head and neck. Histologically, DEC shares similar features to invasive breast carcinoma, thus causing great diagnostic challenges. We report a 69-year-old woman who presented with a hardened plaque on the axilla. A skin biopsy was performed and metastatic invasive breast carcinoma could not be ruled out. Complete excision and further workup were subsequently conducted, leading to the diagnosis of estrogen receptor positive DEC with associated axillary lymph node metastases. The patient received adjuvant radiotherapy to the left axilla and was started on oral letrozole. She is disease-free 14 months after initial diagnosis.